1998
DOI: 10.1038/sj.ijo.0800744
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alcohol consumption and various beverages on waist girth and waist-to-hip ratio in a sample of French men and women

Abstract: OBJECTIVE: The goal of the present study was to assess the association between alcohol consumption and abdominal fat deposition in France, a country where wine is the most commonly consumed alcoholic beverage. METHODS: We analyzed the association between alcohol consumption and various markers of body weight, in a population sample recruited in three distinct geographical areas of France (MONICA centers). This sample included men (n 1778) and women (n 1730) aged 35 ± 64 y, randomly selected from electoral roll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
68
2
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 8 publications
16
68
2
7
Order By: Relevance
“…Earlier findings on the effect of alcohol intake on abdominal obesity have not been consistent (Sakurai et al, 1997;Dallongeville et al, 1998;Lahmann et al, 2000). Similarly, some authors have observed that smoking is associated with abdominal obesity (Seidell et al, 1991), which was not found here.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Earlier findings on the effect of alcohol intake on abdominal obesity have not been consistent (Sakurai et al, 1997;Dallongeville et al, 1998;Lahmann et al, 2000). Similarly, some authors have observed that smoking is associated with abdominal obesity (Seidell et al, 1991), which was not found here.…”
Section: Discussioncontrasting
confidence: 58%
“…All in all, BMI is nevertheless one of the most marked determinants of WHR (Molarius et al, 1999;Lahti-Koski et al, 2000a;Kuh et al, 2002). Apart from its inverse relation to social class (Brunner et al, 1998;Lahmann et al, 2000) and level of education (Marti et al, 1991;LahtiKoski et al, 2000a), WHR has been shown to be associated with several lifestyle factors, such as alcohol consumption (Laws et al, 1990;Sakurai et al, 1997;Dallongeville et al, 1998), smoking (Laws et al, 1990), high intake of dietary saturated fats (Ward et al, 1994), physical inactivity (Laws et al, 1990;Trichopoulou et al, 2001), increased stress and anxiety (Lloyd et al, 1996), shiftwork (van Amelsvoort et al, 1999) and parity (Lahmann et al, 2000). These studies, however, have not taken simultaneously into account earlier lifecourse variables, for example, body size at different ages.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in a subsample of the US Cancer Prevention Study II, there was no clear association between beer intake and 10 y changes in 'weight gain at the waist' in men or women, and beer intake was negatively associated with 10 y changes in BMI in both genders (Kahn et al, 1997). In a French study, beer (and wine) intake was positively associated with WHR in women but not in men, and inversely with BMI in women (Dallongeville et al, 1998). In Swedish women, WHR correlated negatively with consumption of beer (and wine) (Rosmond & Bjorntorp, 1999).…”
Section: Discussionmentioning
confidence: 79%
“…The literature on the relation of beer-to-obesity indices is sparse and inconsistent (Slattery et al, 1992;Duncan et al, 1995;Kahn et al, 1997;Dallongeville et al, 1998;Rosmond & Bjorntorp, 1999). Since obesity, particularly abdominal, is a strong risk factor for cardiovascular disease (Larsson, 1992), and beer is becoming increasingly popular, we thought that this question deserves some attention.…”
Section: Introductionmentioning
confidence: 99%
“…A recent prospective population study found that an increased WC in both men and women was associated with the consumption of spirits, but not wine intake. 64 Alcohol consumption has found to be associated with a larger WC and higher WHR regardless of BMI in both genders, 65 and male and female heavy drinkers have been found to have a larger WC than expected from their BMI in comparison with occasional drinkers. 66 Alcohol consumption and smoking have also been found to be significantly associated with central adiposity measured on the basis of the ratio of iliac and thigh circumferences in middle-aged French men.…”
Section: Discussionmentioning
confidence: 95%